Mr. Ricardo's Great Adventure : Estimating Fiscal Multipliers in a Truly Intertemporal Model - Sgherri, Silvia (IMF Working Papers; Working Paper ;, 2006)
We estimate tax multipliers in a "Blanchard-Yaari" consumption model where Ricardian equivalence is broken because the private sector discounts the future at a faster rate than the real rate of interest. The model fits U.S. data since 1955 extremely well-entailing a discount wedge of around 20 percent a year and fiscal multipliers of 0.15-0.4-depending on the permanence of the change in taxes/transfers, and is much superior to one that assumes some consumers are fully Ricardian and others follow simple rules of thumb. The implied high private sector rate of discount has wide implications for policymakers.